Analysis of Ore Hand-Crushed Size Distribution for Grinding Process in the Artisanal and Small-Scale Gold Mines Production: A Case Study of Nholi Mine, Bahi District - Tembo, Malugu M.; Mdee, Ombeni J. (Tanzania Journal of Engineering and Technology, 2023)
In many parts of the world, artisanal and small-scale gold mines (ASGM) employed numbers of people compared to large-scale mines. The ASGM has been played a crucial role in poverty alleviation and rural development, particularly in developing countries. The mined ore is crushed and ground for beneficiation of gold. The grinding process involved the size reduction of blasted materials to acquire minerals of interest. This paper presents the size distribution of hand-crushed for blasted materials using sieve analysis and digital image processing. The sieve test results for hand-crushed blasted material of three muck-piles were ranged between 17 mm and 36 mm that is equivalent to 20% and 80% passings respectively, with an average of 26 mm. The digital image processing results were about 19.8 mm for 20% passing and 58 mm for 80% passing, with an average of 36.06 mm. The hand-crushed provided a wide range of material distribution than the required size in the grinding unit and increased oversize by 18%. The hand-crushed of blasted materials provides different sizes distribution leading to increase the residence time and power consumption of the grinding units. Keywords: Artisanal, Small-scale Gold Mines, hand-crushed rock, sieve test, digital image processing, and grinding.